Kreativitas Guru Mengelola Laboratorium (Hubungan Kreativitas Guru dengan Efektivitas Guru Mengelola Laboratorium IPA SMU di Kotamadya Pekanbaru) (Jurnal Pilar Sains, 2005)
The objective of research is to analyze the relationship between teacher’s creativities and theireffectiveness in managing science laboratoty of senior high school in Pekanbaru. The sample of theresearch is 30 of respondents selected randomly. The research concludes that there is positive correlationbetween; teacher’s creativities (X) and their effectiveness in managing laboratory (Y). Furthermore,there is a positive correlation between teacher’s creativities and their effectiveness in managing scienceslaboratory of senior high school in Pekanbaru.